Analysis of Blocking Skills of Bolavoli Players at Smp Negeri 7 Bermani Ilir Extracurricular Students - Putra, Satria Adi; Martiani, Martiani; Sumantri, Ajis (Journal of Physical Education and Sports, 2024)
The purpose of this study was to discuss research to determine the Blocking Ability of Bolavoli Players of students at SMP Negeri 7 Bermani Ilir. The research method used is a survey using tests. The population was 20 male students and the sample in this study used purposive sampling, namely all students at SMP Negeri 7 Bermani Ilir as many as 20 students. The data collection method used in this study was a measurement test. The data analysis technique used is descriptive percentage statistics. The results for the "very high" category were 2 students or 10.00%; "high" category were 4 students or 20.00%; "medium" category were 6 students or 30.00%; "low" category were 8 students or 40.00%; and "very low" category were 0 students or 0.0%. The overall conclusion is in the Lack category.